2010
DOI: 10.1128/cmr.00006-09
|View full text |Cite
|
Sign up to set email alerts
|

Using Epstein-Barr Viral Load Assays To Diagnose, Monitor, and Prevent Posttransplant Lymphoproliferative Disorder

Abstract: SUMMARYEpstein-Barr virus (EBV) DNA measurement is being incorporated into routine medical practice to help diagnose, monitor, and predict posttransplant lymphoproliferative disorder (PTLD) in immunocompromised graft recipients. PTLD is an aggressive neoplasm that almost always harbors EBV DNA within the neoplastic lymphocytes, and it is often fatal if not recognized and treated promptly. Validated protocols, commercial reagents, and automated instruments facilitate implementation of EBV load assays by real-ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
157
0
10

Year Published

2014
2014
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 209 publications
(177 citation statements)
references
References 200 publications
3
157
0
10
Order By: Relevance
“…The data showed that the median of maximum viral loads were significantly higher in the PTLD patients (4035 copies/mL) than nonaffected patients (500 copies/mL), consistent with several previous studies. [3][4][5] As we detected in this study, a wide range of EBV loads were observed in liver transplant patients. This was because of involvement of multiple host factors such as age of transplant, active primary infection, different underlying disease, immunosuppressive drug regimen, and intensity.…”
Section: Discussionsupporting
confidence: 49%
See 3 more Smart Citations
“…The data showed that the median of maximum viral loads were significantly higher in the PTLD patients (4035 copies/mL) than nonaffected patients (500 copies/mL), consistent with several previous studies. [3][4][5] As we detected in this study, a wide range of EBV loads were observed in liver transplant patients. This was because of involvement of multiple host factors such as age of transplant, active primary infection, different underlying disease, immunosuppressive drug regimen, and intensity.…”
Section: Discussionsupporting
confidence: 49%
“…31,35 As shown in several studies, the incidence of PTLD is higher in pediatric than adult liver transplant patients. [1][2][3] The Scientific Registry of Transplant Recipients (SRTR) reported that 82% PTLDs occur in children aged < 17 years. 36 In the current study, more than 88% (30 of 34 patients) of PTLD cases occurred in children aged < 12 years.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Quantification of the plasma EBV-DNA level may facilitate the monitoring of treatment response and it has been found to be effective in different types of lymphoproliferative diseases (13)(14)(15). For cases responding to treatment, circulating EBV-DNA falls to undetectable levels when complete remission is achieved (13).…”
Section: Discussionmentioning
confidence: 99%